Prácticas editoriales y culturales en el Gran La Plata (2015-2021): Entrevistas - Bonfiglio, Florencia (Gran La Plata, 2023)
Editorial and cultural practices in Greater La Plata (2015-2021) compiles interviews conducted between March 2020 and November 2021 with independent publishers, booksellers, teachers, artists, poets and storytellers of our region who in recent years have undertaken or given continuity to relevant projects not only in the literary, artistic and publishing fields, but also related to the use of the spoken word in the public space, with a deeply transformative vocation. The book intends to make a contribution to socio-cultural studies on our region, as it exposes part of the results of the Project Executing Unit (CONICET) "Social heterogeneity, socio-political conflicts and public policies in Greater La Plata (2015-2019)" based in Instituto de Investigaciones en Humanidades y Ciencias Sociales, IdIHCS-UNLP/CONICET. Its object of analysis is the number of recent transformations in Argentine society, within the broader context of changes in the capitalist development model and the processes of globalization and glocalization, which the series of interviews seeks to survey.